A Highly Sensitive, Reversible, and Bidirectional Humidity Actuator by Calcium Carbonate Ionic Oligomers Incorporated Poly(Vinylidene Fluoride). (20th April 2021) - He, Yan; Kong, Kangren; Guo, Zhengxi; Fang, Weifeng; Ma, Zaiqiang; Pan, Haihua; Tang, Ruikang; Liu, Zhaoming
Abstract: Sensitivity and multi‐directional motivation are major two factors for developing optimized humidity‐response materials, which are promising for sensing, energy production, etc. Organic functional groups are commonly used as the water sensitive units through hydrogen bond interactions with water molecules in actuators. The multi‐coordination ability of inorganic ions implies that the inorganic ionic compounds are potentially superior water sensitive units. However, the particle forms of inorganic ionic compounds produced by classical nucleation limit the number of exposed ions to interact with water. Recent progress on the inorganic ionic oligomers has broken through the limitation of classical nucleation, and realized the molecular‐scaled incorporation of inorganic ionic compounds into an organic matrix. Here, the incorporation of hydrophilic calcium carbonate ionic oligomers into hydrophobic poly(vinylidene fluoride) (PVDF) is demonstrated. The ultra‐small calcium carbonate oligomers within a PVDF film endow it with an ultra‐sensitive, reversible, and bidirectional response. The motivation ability is superior to other bidirectional humidity‐actuators at present, which realizes self‐motivation on an ice surface, converting the chemical potential energy of the humidity gradient from ice to kinetic energy. Abstract : The humidity actuator is an important kind of smart device in advanced materials. By the utility of inorganic ionic oligomers as the water sensitive units, a humidity actuator utilizing a hydrophilic inorganic–hydrophobic organic system is reported, which yields an ultra‐sensitive, reversible, and bidirectional response, leading to the dancing of this actuator on an ice surface.